Long-term follow-up evaluation of autologous chondrocyte implantation for symptomatic cartilage lesions of the knee: A single-centre prospective study. Issue 10 (October 2017) - Berruto, M.; Ferrua, P.; Pasqualotto, S.; Uboldi, F.; Maione, A.; Tradati, D.; Usellini, E.
Abstract: Introduction: Autologous Chondrocyte Implantation (ACI) has been the first technique in reconstruction of a valid articular surface. The aim of this study was to evaluate clinical results of this technique at an average follow up of 162 ± 27 months (range 88–208) in a group of patients who underwent ACI. Materials and methods: 32 patients were operated between 1997 and 2007 for chondral lesions or osteochondritis dissecans of the knee. Mean size of the defect was 5.48 cm 2 ± 1.53 (range 2–9). Nine patients were treated with I generation technique and 23 with II generation. All patients were evaluated with Subjective IKDC and Tegner Activity Scales for clinical outcomes and with EQ-VAS for a quantitative measure of health after intervention, starting from pre-operative period and at regular follow up (minimum 88 months-maximum 208 months). Results: A significant increment of all scores was noticed comparing preoperative and postoperative results. In particular medium IKDC score increased from 40.3 ± 9.6 in preoperative evaluation to 74.2 ± 11.6 at one year (p < 0.00001) and to 83.9 ± 10.4 at 5 years follow up (p < 0.001). Mean IKDC values at the last follow-up were 80.3 ± 14.2, showing no statistical differences with those obtained at five-year follow-up. Tegner Activity Scale values increased from 2.8 ± 1.1 preoperatively to 4.1 ± 1.1 (p < 0.0001) after one year and to 6 ± 1.1 at five years (p < 0.0001). Mean Tegner Activity Scale values decreased to 4.8 ± 1.4 at the last follow-up. EQ-VAS evaluation showed superposable results comparing the 5 years evaluation with the ones at a medium follow up of 162 ± 27 months. Discussion: The most important finding is the reliability at long-term of ACI technique, which in our series gave excellent clinical results. No statistical differences were observed between first- and second-generation. Clinical outcomes were significantly better for defects in the femoral condyles, influenced by age (worse results over 30 years old). Conclusions: ACI represents a valid technique for chondral and osteochondral lesions of the knee in a population heterogeneous for age, sex and activity level with good results even at a long term follow up.